KEMUNCULAN DAN RAGAM LEMBAGA PENDIDIKAN ISLAM DI NUSANTARA PADA MASA PRA-KOLONIAL BELANDA DALAM PERSPEKTIF SOSIAL POLITIK - Kesty Amia Zora; Jamrizal; Salahuddin (Jurnal Genta Mulia, 2026)
This study aims to analyze the emergence and variety of Islamic educational institutions in the Nusantara during the pre-Dutch colonial period (13th–16th centuries) and to examine the influence of social and political factors on their development. This research uses a qualitative method with a library research approach and descriptive-analytical analysis of various relevant scientific literature sources. The study results indicate that the emergence of Islamic educational institutions was part of the Islamization process, which occurred gradually through trade, social, and cultural interactions. Educational institutions developed in various forms such as surau, pesantren, dayah, meunasah, and langgar, which adapted to local conditions. Social factors such as the need for religious education, interaction with Muslim traders, the role of scholars, and community development became the main drivers, while political factors such as support from Islamic kingdoms, the integration of power and religion, and scholar networks strengthened legitimacy and continuity. In conclusion, Islamic educational institutions in the pre-colonial period not only functioned as centers of religious education, but also as part of the socio-political system that played a role in shaping the character of society and the structure of power.